Acceleration feedback control (AFC) enhanced by disturbance observation and compensation (DOC) for high precision tracking in telescope systems. (August 2016) - Wang, Qiang; Cai, Hua-Xiang; Huang, Yong-Mei; Ge, Liang; Tang, Tao; Su, Yan-Rui; Liu, Xiang; Li, Jin-Ying; He, Dong; Du, Sheng-Ping; Ling, Yu
Abstract: In this paper, a cascade acceleration feedback control (AFC) enhanced by a disturbance observation and compensation (DOC) method is proposed to improve the tracking precision of telescope systems. Telescope systems usually suffer some uncertain disturbances, such as wind load, nonlinear friction and other unknown disturbances. To ensure tracking precision, an acceleration feedback loop which can increase the stiffness of such a system is introduced. Moreover, to further improve the tracking precision, we introduce the DOC method which can accurately estimate the disturbance and compensate it. Furthermore, the analysis of tracking accuracy used by this method is proposed. Finally, a few comparative experimental results show that the proposed control method has excellent performance for reducing the tracking error of a telescope system.